Isotopic enrichment of Zn particles by laser ablation - Felix Pozzi, Marcelo Nicolas (2017)
The use of Zn in nuclear reactors reduces the amount of 60Co generated as a consequence of the natural activation of Co. On the other hand, isotopically enriched Zn can be used as a tracer in biological systems. At the present, the enrichment of Zn is obtained using gaseous compounds of the metal by centrifugal force. In this paper, we present a method based on laser ablation of metallic targets of Zn with a Nd?YAG nanosecond laser to produce isotopically enriched Zn particles. Also, the effect of the wavelength irradiation laser on the enrichment factor was studied and a procedure is proposed to collect the different enrichment fractions yield.